Effects of aerobic exercise on cognitive function in older adults with mild cognitive impairment: a systematic review and meta-analysis - Zhao, Qian; Hong, Zhao Chen; Wei, Tian Tian; Jiang, Yu Ting; Zeng, Hui; Miao, Guiling (Frontiers in Psychiatry, 2026)
BackgroundRegular exercise may boost cognition in older adults with MCI, but the effectiveness of different aerobic exercise (AE) modalities is unclear. We conducted a meta-analysis to assess AE’s impact on cognition in this group.ObjectiveThis systematic review and meta-analysis aimed to evaluate the effects of AE on cognitive function in older adults with MCI.MethodsWe searched PubMed, Embase, Web of Science, and the Cochrane Library up to July 2025 and referenced included articles. RCTs with aerobic exercise and outcomes for global cognition and specific cognitive domains in older MCI adults were included. Data was pooled using mean difference, standardized random-effect model, and 95% CI with RevMan V.5.4 and Stata 16.0.ResultsA total of 33 studies with 1996 participants were included. The results revealed that AE exerted a significant positive effect on global cognition (SMD = 0.81, 95% CI (0.50, 1.12), Z = 5.07, p=0.00) and a moderate positive effect on memory (SMD = 0.34, 95% CI (0.06, 0.63); Z = 2.33, p = 0.02). Notably, no significant improvements were observed in executive function, attention, processing speed, language, or visuospatial abilities. Furthermore, meta-regression and subgroup analyses indicated statistically significant variations across different intervention combinations, suggesting heterogeneity in treatment effects.ConclusionAE significantly improved global cognition and memory in elderly individuals with MCI. Furthermore, the frequency (3–5 sessions per week), timing, intensity, and total duration of the interventions should be tailored to individual needs and gradually refined for personalized optimization.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021238308.